When is cash good or bad for firm performance?. (4th February 2016) - Deb, Palash; David, Parthiban; O'Brien, Jonathan
Abstract : Research summary: Cash can create shareholder value when used for adaptation to unfolding contingencies, but can also reduce value when appropriated by other stakeholders. We synthesize arguments from the behavioral theory of the firm, economic perspectives like agency theory, and the value‐creation versus value‐appropriation literatures to argue that the implications of cash for firm performance are context‐specific. Cash is more beneficial for firms operating in highly competitive, research‐intensive, or growth‐focused industries that are typical of contexts requiring adaptation in the face of uncertainties. Conversely, cash is more detrimental to performance in firms that are poorly governed, diversified, or opaque, as are typical of contexts where stakeholder conflicts, information asymmetries, or power imbalances can encourage value appropriation by other stakeholders. Managerial summary: Cash can create shareholder value when used for adaptation to unfolding contingencies, but can also reduce value when appropriated by other stakeholders. While cash‐rich firms have higher performance on average, with those in the 75th percentile having a market‐to‐book value 15 percent higher than those in the 25th percentile, we find that the performance benefits of cash depend on the context. Cash is more beneficial for firms operating in highly competitive, research‐intensive, or growth‐focused industries that are typical of contexts requiring adaptation in the face of uncertainties. Conversely, cash is more detrimental to performance in firms that are poorly governed, diversified, or opaque, as are typical of contexts where stakeholder conflicts, information asymmetries, or power imbalances can encourage value appropriation by other stakeholders . Copyright © 2015 John Wiley & Sons, Ltd.